(untitled) (Bangladesh Journal of Nutrition, 2021)
Students, particularly female students, living in university dormitories are susceptible to various nutritional deficiencies due to their improper dietary practice and poor diet quality. Whether food originates from animal or plant sources contributes greatly to the quality of their diets in terms of nutritional adequacy. This study made a bioavailability assessment of four nutrients (vitamin A, iron, protein, and zinc) from students’ diets followed by examining whether bioavailability relates to the animal/plant ratio (A/P) in the diets of female residential students (FRS) of Bangladesh. Previously published dietary algorithms or conversion factors specific to different food groups were used to assess nutrient bioavailability in the diets of 180 (60 for iron) FRS of the University of Dhaka. Nutrient inadequacy was evaluated using i) an individual diet approach (estimating bioavailability from individual diets), and ii) a dietary pattern approach (presuming average bioavailability for mixed diets). The mean absorptions of iron and zinc, quality of protein, and conversion factor for β-carotene were 15.5%, 35.1%, 66.1%, and 17:1, respectively. Among the individual diets, a large range in bioavailability was observed, which was explained inadequately by their A/P. There was a significant difference in inadequacy prevalence when iron and protein bioavailability from individual diets were compared with bioavailability estimates calculated applying average conversion factors for mixed diets. The A/P could not necessarily predict the nutrient bioavailability in FRS diets. Hence, it is important to consider the diet composition when evaluating nutrient adequacy in the diets of FRS and other students. Bangladesh J. Nutr. Vol. 34, December 2020, P: 55-64